Interpretation of legal duty in the American legal tradition - Терезія Попович; Вікторія Вашкович (Конституційно-правові академічні студії, 2024)
Human rights, as enshrined in current international legal instruments, are the result of long-term historical development and the gradual formation of standards that have become the norm in modern democratic society. The formation of such unified standards for regulating social life has led to the modern doctrine of human rights being based on universal principles and values, including freedom, equality, justice, and the inalienability of fundamental human rights. However, despite the commonality of these values and principles on which the modern idea of human rights is founded, its formation and gradual development occurred under the influence of cultural, historical, political, and sociological factors of individual states or entire regions. These factors led to the emergence of distinct legal traditions.